Reforming Arabic Reading Instruction with Problem-Based Learning: A Classroom-Based Study - Ratna Komalasari; Muhammad Al- Kaosari; Liazi Maulidi; Ardia Pramesti Regita Cahyani; Fathul Maujud (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study examines the effectiveness of a Problem-Based Learning (PBL) strategy in enhancing the Arabic reading skills of Baitul Qur’an students. The problem addressed in this research is the persistent difficulty students face in memorizing and understanding Arabic vocabulary, which stems from limited practice and insufficient active engagement during learning activities. The main objective of the study is to evaluate how PBL, supported by structured dictionary use, can improve students’ reading comprehension. Employing a qualitative experimental approach, the study implemented a learning model that required students to consistently bring and utilize dictionaries in every Arabic lesson. This practice encouraged students to independently search for meanings and engage with vocabulary more frequently. After identifying the required vocabulary, students applied their understanding through thematic reading tasks, enabling teachers to assess comprehension based on the problems presented. The findings show that eighth-grade students felt more motivated and challenged when engaging in vocabulary-rich reading activities. Overall, the PBL strategy effectively improved students’ reading skills and fostered greater learner autonomy. This study contributes to Arabic language pedagogy by demonstrating that integrating PBL with active vocabulary exploration can serve as a practical method for enhancing reading proficiency in similar educational contexts.